2024
DOI: 10.3390/systems12020051
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Quality Management Methodologies in Wooden Furniture Production

Ewa Skorupińska,
Miloš Hitka,
Maciej Sydor

Abstract: Furniture production is a specific industrial sector with a high human labor demand, a wide range of materials processed, and short production runs caused by high customization of end products. The difficulty of measuring the aesthetic requirements of customers is also specific to furniture. This review of academic papers identifies and explains effective quality management strategies in furniture production. The reviewed literature highlights a range of quality management methodologies, including concurrent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…From the literature review and the four case studies presented, it can be concluded that 3D scanning and reverse engineering have become integral parts of today's industry in cases where new product development and design are needed. It is used in almost all development, design, manufacturing, and quality control aspects [6]. In the case of Bosnia and Herzegovina, it is used extensively in the furniture industry, especially for reverse engineering and design and development of new products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature review and the four case studies presented, it can be concluded that 3D scanning and reverse engineering have become integral parts of today's industry in cases where new product development and design are needed. It is used in almost all development, design, manufacturing, and quality control aspects [6]. In the case of Bosnia and Herzegovina, it is used extensively in the furniture industry, especially for reverse engineering and design and development of new products.…”
Section: Discussionmentioning
confidence: 99%
“…In the furniture industry, constantly creating products with complex shapes and forms presents a challenge for engineers, especially when dealing with prototypes of designer concepts [6]. The prototyping, from concept to final product, often involves multiple iterations due to difficulties in translating the designer's vision into a physical form [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Paperwork is outdated in VSM due to the advent of sensors, software, and real-time data. I4.0 provides high-level integration of lean processes that further contributes to organizational development [24].…”
Section: Integrating Lss and I40 Practicesmentioning
confidence: 99%